Phosphorus and naphthalene acetic acid increased the seed yield by regulating carbon and nitrogen assimilation of flax - Xie, Yaping; Duan, Huirong; Wang, Limin; Zhang, Jianping; Dong, Kongjun; Wang, Xingrong; Zhang, Yanjun; Zhou, Yangchen; Li, Wenjuan; Qi, Yanni; Zhao, Wei; Dang, Zhao; et al. (Frontiers in Plant Science, 2023)
To evaluate the impact of phosphorus (P) combined with exogenous NAA on flax yield, enhance flax P utilization efficiency and productivity, minimize resource inputs and mitigate negative environmental and human effects. Therefore, it is crucial to comprehend the physiological and biochemical responses of flax to P and naphthylacetic acid (NAA) in order to guide future agronomic management strategies for increasing seed yield. A randomized complete block design trial was conducted under semi-arid conditions in Northwest China, using a factorial split-plot to investigate the effects of three P (0, 67.5, and 135.0 kg P2O5 ha -1 ) and three exogenous spray NAA levels (0, 20, and 40 mg NAA L -1 ) on sucrose phosphate synthase (SPS) and diphosphoribulose carboxylase (Rubisco) activities as well as nitrogen (N) and P accumulation and translocation in flax. Results indicated that the SPS and Rubisco activities, N and P accumulation at flowering and maturity along with assimilation and translocation post-flowering, fruiting branches per plant, tillers per plant, capsules per plant, and seed yield were 95, 105, 14, 27, 55, 15, 13, 110, 103, 82, 16, 61, 8, and 13% greater in the P treatments compared to those in the zero P treatment, respectively. Moreover, those characteristics were observed to be greater with exogenous spray NAA treatments compared to that no spray NAA treatment. Additionally, the maximum SPS and Rubisco activities, N and P accumulation, assimilation post-flowering and translocation, capsules per plant, and seed yield were achieved with the application of 67.5 kg P2O5 ha -1 with 20 mg NAA L -1 . Therefore, these findings demonstrate that the appropriate combination of P fertilizer and spray NAA is an effective agronomic management strategy for regulating carbon and nitrogen assimilation by maintaining photosynthetic efficiency in plants to increase flax productivity.